2019
DOI: 10.1055/s-0039-3402788
|View full text |Cite
|
Sign up to set email alerts
|

Clinical criteria for the application of dry needling in myofascial pain Syndrome: An expert consensus document and a cross-sectional study among physical therapists

Abstract: Presently, there is no clear consensus on the essential and confirmatory criteria which should govern the application of dry needling (DN) in the treatment of myofascial trigger points. The aim of this study was to generate a consensus on these criteria, via a panel discussion with DN experts which took place at the International Conference of Invasive Physical Therapy held in 2018, including the opinion of the attendees who participated in a live survey on the subject at the conference via an app. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Previous studies revealed that US fails to identify the exact echogenicity changes [12]. The mechanism of action of DN in pain relief among patients with MPS remains undiscovered [9]. However, therapists can employ needles with an appropriate length to minimize the micro-trauma caused by muscle stimulation; this is due to the effectiveness of this therapeutic technique, the inadequate availability of all muscles, the risk of damage to vessels entering the muscles and the surrounding nerves, and the odds of monitoring muscles through US [10,12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies revealed that US fails to identify the exact echogenicity changes [12]. The mechanism of action of DN in pain relief among patients with MPS remains undiscovered [9]. However, therapists can employ needles with an appropriate length to minimize the micro-trauma caused by muscle stimulation; this is due to the effectiveness of this therapeutic technique, the inadequate availability of all muscles, the risk of damage to vessels entering the muscles and the surrounding nerves, and the odds of monitoring muscles through US [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the International Conference on Invasive Physical Therapy (ICIPT) recommended using US during needling. The safety considerations, visualizing deep tissues and LTR, and recording changes and outcomes were mentioned as the main reasons for applying US [9]. However, the main purpose of US-guided DN is to guide fine needles into deep muscles [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations